A Scientometric Systematic Review of Entrepreneurial Wellbeing Knowledge Production - Contreras-Barraza, Nicolás; Espinosa-Cristia, Juan Felipe; Salazar-Sepulveda, Guido; Vega-Muñoz, Alejandro; Ariza-Montes, Antonio (Frontiers in Psychology, 2021)
This article presents a scientometric study regarding the area of research that studied entrepreneurship and its relationship with wellbeing. The study presents a systematic review and measure the impact and relational character, to put in relevance countries, research organizations and authors in the field of entrepreneurial wellbeing. The studio positions these research questions: What is the nature of the evolution of scientific knowledge in the entrepreneurial well-being field? What is the nature of the concentration in terms of geographical distribution and co-authorship level of knowledge production in the entrepreneurial well-being field? And what are the knowledge trends in knowledge production for the entrepreneurial well-being literature? The contribution of this research it is twofold. First, in terms of methodology, the use of a more robust approach to search for the scientometric trends about entrepreneurship wellbeing in addition to the PRISMA review tools and the PICOS eligibility criteria. Secondly, the present research updates the search for results for the last two years of knowledge production. This upgrade it is particularly important in a research field that presents an exponential growth, where year 2019 and 2020 present almost the double of the knowledge production comparing to year 2017 and 2018.